MiR-27b-3p Inhibition Enhances Browning of Epididymal Fat in High-Fat Diet Induced Obese Mice - Yu, Jing; Lv, Yifan; Wang, Fengliang; Kong, Xiaocen; Di, Wenjuan; Liu, Juan; Sheng, Yunlu; Lv, Shan; Ding, Guoxian (Frontiers in Endocrinology, 2019)
Objective: Long-term dysregulation of energy balance is the key component of the obesity epidemic. Given the harm of central obesity and the discovery that beige cells appear within white adipose tissue (WAT), enhancing the energy-expending or “browning” ability of visceral adipose tissue (VAT) has become of therapeutic interest. In this study, we focused on the regulating role of microRNA (miRNA)-27b-3p in mice epididymal white adipose tissue (eWAT) browning. Methods: High-fat diet (HFD) induced obese mice model was constructed. Expression of miR-27b-3p and Ucp1 in eWAT was measured during the course of HFD. Through tail vein injection of antimiR-27b-3p, miR-27b-3p expression was inhibited to analyze the potential role of miR-27b-3p in fat browning and metabolism. Results: miR-27b-3p was predominantly expressed in eWAT and browning ability of eWAT in HFD induced obese mice was impaired. Inhibition of miR-27b-3p enhanced browning capacity of eWAT in mice fed an HFD and led to weight loss and insulin sensitivity improvement. Conclusions: High expression of miR-27b-3p in eWAT inhibits browning ability and leads to visceral fat accumulation. It is suggested miR-27b-3p may become a potential therapeutic option for visceral obesity and its associated diseases.